High Mass Loading 3D‐Printed Sodium‐Ion Hybrid Capacitors. (11th May 2022) - Yuan, Jun; Qiu, Min; Chen, Jun Xiang; Hu, Xiang; Liu, Yangjie; Yu, Biao; Zhong, Guobao; Weng, Zixiang; Zhan, Hongbing; Wen, Zhenhai
Abstract: Sodium‐ion hybrid capacitors (SIHCs) have been regarded as one of the promising energy devices thanks to its low cost and compromise between energy density and power density, yet remain a challenge towards practical levels of mass loading (>10 mg cm −2 ). Herein, the fabrication of a 1D core–shell structure is reported with N‐doped porous carbon encapsulating ZnV2 O4 nanofibers (ZnV2 O4 NFs@N‐PC), which features an open framework and favorable properties for facilitating ion diffusion, mass transportation, and electron transfer, enabling it to perform impressively for sodium ions storage. A 3D printed SIHC is conceptually proposed by coupling the 3D printed ZnV2 O4 NFs@N‐PC anode with a 3D printed active carbon cathode, which can deliver a high energy/power density of 145.07 Wh kg −1 /3677.1 W kg −1 with a durable cycling lifespan. It is demonstrated that the 3D printed SIHC, even at a high mass loading of up to 16.25 mg cm −2, can release a high areal energy/power density of 1.67 mWh cm −2 /38.96 mW cm −2, outperforming most of the SIHCs developed so far. The present work sheds light on the role of the design of electrode materials and verifies the promise of 3D‐printed technology for next‐generation electrochemical energy devices. Abstract : A 3D printed sodium‐ion hybrid capacitor with a high mass loading of 16.25 mg cm −2 is conceptually proposed by coupling the 3D printed ZnV2 O4 NFs@N‐PC anode with a 3D printed active carbon cathode, which can deliver a high areal energy/power density and exhibit a durable cycling lifespan for 8000 cycles.